Responsiveness to IL-7 but not to IFN-α is diminished in CD4+ T cells from treated HIV infected patients who experience poor CD4+ T-cell recovery. (24th August 2016) - Nguyen, Thao P.; Shukla, Supriya; Asaad, Robert; Freeman, Michael L.; Lederman, Michael M.; Harding, Clifford V.; Sieg, Scott F.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To assess CD4 + T-cell responsiveness to IL-7 and IFN-α in HIV-infected patients who experience poor recovery of CD4 + T-cell counts during therapy (immune failure patients). Design: Responses to IL-7 and IFN-α were compared between HIV-infected immune failure (CD4 + cell counts <379 cells/μl) patients and immune success (CD4 + cell counts >500 cells/μl) as well as healthy control patients. Methods: Flow cytometry was used to assess peripheral blood mononuclear cells for IL-7-induced proliferation, CD25 expression, and signaling (signal transducer and activator of transcription 5 phosphorylation and Akt phosphorylation) in CD4 + T cells. Freshly isolated cells were characterized by expression of IL-7Rα (CD127) among CD4 + T-cell maturation subsets by flow cytometry and sorted CD3 + T cells were assessed for expression of IFN-α and interferon stimulated genes (2′–5′-oligoadenylate synthetase-1 and myxovirus resistance A protein) by quantitative real-time PCR. Responses to IFN-α were assessed by induction of signal transducer and activator of transcription 1 phosphorylation and inhibition of IL-7-induced CD4 + T-cell proliferation. Results: IL-7-induced proliferation and CD25 expression were decreased in CD4 + T cells from immune failure patients. CD127 expressing CD4 + T cells were decreased, whereas expression of 2′–5′-oligoadenylate synthetase-1, myxovirus resistance A protein, and IFN-α mRNA were increased in total CD3 + T cells from immune failure patients. CD127 expression correlated with CD25 induction but not proliferation, whereas T-cell IFN-α mRNA was associated with reduced proliferation in CD4 + T cells from immune failure patients. IFN-α-mediated induction of signal transducer and activator of transcription 1 phosphorylation and inhibition of proliferation were not diminished in CD4 + T cells from immune failure patients. Conclusion: IL-7 responsiveness is impaired in immune failure patients and may be related to expression of CD127 and IFN-α.